PENINGKATAN HASIL BELAJAR KIMIA MELALUI MODEL CHEMISONG PADA PESERTA DIDIK KELAS X KIMIA ANALISIS SMK - Indayatmi, Indayatmi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Abstract This research aims to use learning model chemisong to increase the activity students and learning outcomes in chemistry competency of class X SMK N 2 Depok. Research carried out comprises of three stages: pre-cycle, cycle 1 and cycle 2. Data collection was conducted through observation, evaluation of learning outcomes, assessment chemisong, and documentation. The results showed that the use of chemisong learning model can improve the learning outcomes of students of class X on pre-cycle of learning evaluation values obtained by an average of 51, cycle 1 by 73, cycles 2 of 82. The use of the learning model chemisong can increase the number of learners who on pre-cycle can increase the number of learner who achieve minimum scor criteria minimum of 4 students on cycle 1 of 19 students on cycle 2 of 27 students. The conclusion of this study is the use chemisong learning model can improve the activity of the learner and the learning outcomes chemistry on students of class X SMK N 2 Depok. Keywords: chemisong; chemical; activity; learning outcomes Abstrak Penelitian ini bertujuan menggunakan model pembelajaran chemisong untuk meningkatkan aktivitas peserta didik dan hasil belajar pada kompetensi kimia kelas X SMK Negeri 2 Depok. Penelitian yang dilakukan terdiri dari 3 tahap yaitu pra siklus, siklus 1, dan siklus 2. Pengumpulan data dilakukan melalui observasi, evaluasi hasil belajar, penilaian chemisong, dan dokumentasi. Hasil penelitian menunjukkan bahwa penggunaan model pembelajaran chemisong dapat meningkatkan hasil belajar peserta didik kelas X yaitu pada pra siklus diperoleh nilai evaluasi belajar rata-rata sebesar 51, siklus 1 sebesar 73, siklus 2 sebesar 82. Penggunaan model pembelajaran chemisong dapat meningkatkan jumlah peserta didik yang mencapai kriteria ketuntasan minimal yaitu pada pra siklus sebanyak 4 peserta didik, siklus 1 sebanyak 19 peserta didik, siklus 2 sebanyak 27 peserta didik. Kesimpulan penelitian ini adalah penggunaan model pembelajaran chemisong dapat meningkatkan aktivitas peserta didik dan hasil belajar kimia pada peserta didik kelas X SMK N 2 Depok. Kata Kunci: chemisong; kimia; aktivitas; hasil belajarÂ Permalink/DOI: http://dx.doi.org/10.15408/es.v9i1.2878 Â